Levels of Galectin-7 in serum and sputum in children with asthma - Xu, Y L (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To observe the expression of Galectin-7 in the serum and sputum of asthmatic children and to explore its significance in asthmatic children. Methods: The study prospectively case-control selected 183 children diagnosed with bronchial asthma at Department Ⅱ of Respiratory Medicine, National Clinical Research Center for Respiratory Diseases, Beijing Children's Hospital of Capital Medical University. The control group consisted of 41 children with other bronchial diseases and 43 healthy children. Children in the asthma group were divided into acute and non-acute exacerbation groups. Acute exacerbation group was divided as mild acute, moderate acute and severe acute groups; non-acute exacerbation group was divided as mild persistent, moderate persistent and severe persistent groups. Children without acute exacerbation asthma in the asthma group were divided into high and low Galectin-7 groups based on median serum Galectin-7 levels. Serum and sputum were collected, Galectin-7 levels were measured using enzyme-linked immunosorbent assay. The study compared and analyzed the differences in Galectin-7 levels between children with asthma and the control groups using Mann-Whitney U test or the Kruskal-Wallis or the Chi-square test for inter-group comparisons. Results: Among 183 children, 61 cases had acute asthma exacerbation, and 122 cases had persistent asthma without acute exacerbation. The asthma group comprised 110 males and 73 females. The control group consisted of 41 children with other bronchial diseases, including 24 cases of bronchiectasis and 17 cases of obliterans bronchitis. The control group comprised 26 males and 15 females. Forty-three healthy children who underwent physical examination, including 22 males and 21 females. The levels of Galectin-7 in serum were significantly higher in children with an acute asthma exacerbation than that of healthy children (0.1 (0, 0.7) vs. 0 (0, 0.2) μg/L, Z=2.09, P=0.001). Galectin-7 levels in sputum were higher in children with an acute asthma exacerbation than that in children with other bronchial diseases (1.2 (0.1,3.7) vs. 0.4 (0.1, 1.5) μg/L, Z=2.20, P<0.001). Serum Galectin-7 levels were significantly higher in children with persistent asthma compared to children with other bronchial diseases and healthy children (0.6 (0.3, 1.2) vs. 0.1 (0, 0.5) and 0 (0, 0.2) μg/L, Z=-6.12,-7.63, both P<0.001), and the levels were significantly and positively correlated with asthma severity (r=0.77, P<0.001), disease duration (r=0.34, P=0.001), and number of previous attacks (r=0.51, P<0.001). There were 61 children in the high-Galectin-7 group and 61 children in the low-Galectin-7 group. Children with high Galectin-7 had more asthma triggers, a greater proportion with a positive family history, more previous asthma attacks, longer duration of asthma, and higher serum total IgE levels compared to those with low Galectin-7 (χ2=9.30, 22.46, Z=5.06, 3.57, 2.31, all P<0.05). Conclusion: The expression of Galectin-7 is found to be elevated in the serum and sputum of asthmatic children and correlated with asthma conditions